(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
The paper presents the author’s experience in supporting laboratory applications in the discipline of Electric Machines during the pandemic caused by the SARS-CoV-2 virus, when the teaching hours took place online, similar to the specific activities of the distance education system. The experiments within the laboratory works are simulated in the MATLAB-Simulink computing environment by using and adapting the models of transformers and electric machines, existing in the SimPowerSystem library. The concept of numerical applications was made so that the implementation of electrical diagrams is performed by students, given that they have no experience in numerical modeling of electrical machines. Several methods for obtaining the results from numerical experiments are presented, which allow ensuring a balance between the number of data specific to each work and the necessary calculation effort so that the experiments can be performed in the time allotted to a work of laboratory.